Peningkatan Kreativitas Siswa Dalam Pembuatan Media Pembelajaran Interaktif CSS JavaScript Melalui Make a Match - Titik Dian Darmayanti; Syaad Pathmantara; Mahali Mahali (Nucleus Journal, 2026)
This research is entitled: " Improving Student Creativity in Creating Interactive CSS JavaScript Learning Media Through Make a Match ". The purpose of this study is to enhance students' creativity in developing interactive learning media using CSS and JavaScript by implementing the Make A Match cooperative learning technique in the Software and Game Development subject for class X-PPLG 2 at SMK Negeri 5 Malang. The research method employed is classroom action research comprising three cycles, each involving Planning, Implementation, Observation, and Reflection. The findings indicate that the use of the Make A Match cooperative learning method has been effective in improving various aspects of student learning, including creativity, motivation, active participation, presentation skills, and discipline. The consistent improvement in grades also suggests that this method can sustain students' interest and engagement in the learning process, thereby positively impacting their learning outcomes. Furthermore, the study recommends that teachers facing similar challenges consider implementing the Make A Match cooperative learning method to enhance student creativity. Additionally, teachers are encouraged to design learning materials in a more creative and innovative manner to maximize the benefits of Make A Match Cooperative Learning.